Revision of the alderfly genus Indosialis Lestage (Megaloptera: Sialidae) - Liu, Xingyue; Flint, Oliver. Jr S.; Yang, Ding (Zootaxa, 2008)
Indosialis Lestage is a small Asian genus of alderflies. Herein, we describe a new species, I. indicus, and revise the three species in the genus. A key to males and a discussion of the phylogeny and biogeography of the genus is provided.